2018
DOI: 10.1055/s-0044-101827
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Optical Coherence Tomography for the Detection of Early Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is one of the leading causes of vision loss globally with a severe burden on all societies due to its high treatment and rehabilitation costs. The early diagnosis of DR may provide preventive steps (including retinal laser therapy and tight carbohydrate, blood pressure, and cholesterol control) that could in turn help to avoid progression of the pathology with the resultant vision loss. Optical coherence tomography (OCT) enables the in vivo structural imaging of the retina, providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
3
0
1
Order By: Relevance
“…According to previous studies 2,4,5 , thickness changes were observed in different retinal layers and in different regions in the macula of diabetic and DR patients. Furthermore, it was found that OCT is able to detect early neurodegenerative changes in diabetic patients when DR is non-detectable using fundus exams 6 . This implies that OCT data is of great value to the early detection and better understanding of DR.…”
mentioning
confidence: 99%
“…According to previous studies 2,4,5 , thickness changes were observed in different retinal layers and in different regions in the macula of diabetic and DR patients. Furthermore, it was found that OCT is able to detect early neurodegenerative changes in diabetic patients when DR is non-detectable using fundus exams 6 . This implies that OCT data is of great value to the early detection and better understanding of DR.…”
mentioning
confidence: 99%
“…As a rapid non-invasive imaging technique, optical coherence tomography (OCT) can present ''optical biopsy'' of the posterior segment of eyes and measure macular thickness in a quantitative way, which contributes to the diagnoses and follow-up of fundus oculi diseases. [1][2][3] The changes in macular thickness occur in eyes with retinal diseases, such as diabetic retinopathy (DR), neurovascular agerelated macular degeneration and retinal vein occlusion, which could induce macular thickening or oedema and geographic atrophy, macular atrophy, which could induce macular thinning.…”
Section: Introductionmentioning
confidence: 99%
“…Research in different areas of complications associated to DM is constantly evolving (Campagnoli et al, 2017 ; Somfai et al, 2018 ). The search for risk biomarkers characterizing preclinical abnormalities is fundamental to fast-track the discovery of novel treatments.…”
Section: Introductionmentioning
confidence: 99%